Regional Diversification of Saturation of the Housing Stock. Poland against the Background of Europe - Jacek Łaszek; Krzysztof Olszewski; Joanna Waszczuk (Barometr Regionalny)
The aim of the article is to present the differences in saturation of the housing stock and its availability in Poland as well as in European Union countries and its influence on house prices and the economy. Regions which are characterized by a housing shortage will be separated. The analysis takes into account the differences in the level of wealth of the inhabitants and the scale of urbanization of individual states. The implications of social and economic imperfections in the functioning of the housing market, and in particular the price volatility of housing, have also been addressed. In addition, the quantitative and qualitative differences in the housing stock, which reduce the effective stock of available housing, are highlighted. In the case of Poland, only in Warsaw and Łódź does housing saturation correspond to that of the “old” EU. This article is divided into 5 parts. After an introduction to the subject, the second section deals with the issues of structural, long-term imbalances of demand and supply in the European housing market and its consequences. In the third section, the housing situation in the EU is presented. In the fourth part, the regional diversification in the housing stock in Poland is discussed. Section five consists of conclusions and a summary of the analysis.